Creative Indigenous Technologies in the Transformation of the Groundnut Industry in Central Nigeria (Global Journal of Human-Social Science, 2016)
Nations of the Asian Tigers, as far back as the 19th and 20th centuries, came to realize and recognize the fundamental role that indigenous technology in the field of commercial agricultural revolution. The Asian tigers, namely, Japan, Korea, China, Indonesia, Malaysia, evolved indigenous technologies overtime which came to serve as the technological base station in the drive for overcoming the hurdles of traditional based economy whose techniques of production were rooted in traditional beliefs and ideas. In this paper, Nigeria has a lot to adopt from the framework of the Asian Tigers if the nation must overcome the challenges of a traditional based economy which depends primarily on primitive crude forces of production. Already, in several fields of her national history, particularly the agricultural sector, there is the invention and evolution of indigenous technologies in the agro-allied sector which can become the panacea for an agricultural driven revolution. This paper focuses in the evolution of indigenous technologies in the processing and production of groundnut, yams and cereals.
Keywords: The Asian tigers; namely; Japan; Korea; China; Indonesia; Malaysia; evolved indigenous technologies